Investigations of tribodynamic characteristics of chrome steel pin against plain and textured surface cast iron discs in lubricated conditions. (15th July 2019) - Lal, Roop; Singh, R.C.
Abstract : Purpose: The purpose of this paper was to carry out an experimental study to investigate tribodynamics at the interface of chrome steel pin with the plain and textured surface cast iron discs in a fully flooded condition. Design/methodology/approach: A friction and wear tester (tribometer) was used for conducting the experiment at different operating parameters. Lubricating oil used in this experiment was SAE-15W40, which directly supplied at the interface and ensured a fully flooded lubricating condition. Measurements of different parameters, such as friction coefficient, the rate of wear, the amplitude of vibration, rise in temperature and intensity of sound, were considered at different loads. The input parameters were taken in a range viz. Loads from 1.9 MPa to 3.1 MPa, sliding speeds from 2 to 10 m/s and distance travelled ranged from 1000 to 5000 m. Findings: In the investigation, it was found that there was a decrease in friction coefficient and wear rate at the interface formed by the chrome steel pin with textured surface cast iron disc when compared with friction coefficient and wear rate at the interface formed by the chrome steel pin and the plain surface disc of cast iron. Originality/value: Also, it was inferred that temperature, vibration and noise level, at the interface formed by the chrome steel pin and plain surface cast iron disc, increased, which governed the interface stability. The novelty of this investigation lies in the identification of the parameters on which interface stability depends.